(untitled) (Revista Direito em Debate, 2024)
Racism runs through the entire history of Brazil, revealing itself as an instrument of the State in the exercise of biopolitics, so that it is embedded in society and in all structures of the Brazilian State itself, including in police institutions that end up acting selectively against the black population, which produces true necropolitics. In this context, Jessé Souza’s conception of multidimensional racism is revealed, which is outlined by a set of oppressive actions that humiliate black people within society, under the cover of different disguises considering the social context, including repressive action-punitive from the State. In addition, constant technological evolution has promoted significant advances in digital technologies, especially through the use of AI, big data, IoT, among others that, in the area of public security, show promise with the development of predictive systems which allows for a more effective allocation of resources in crime prevention. This article sought to respond to the importance of transparency and control of the police state in the use of predictive policing due to racial discriminatory bias. To this end, a survey of existing studies was carried out on the use of new digital technologies in predictive policing systems. As a result, there was a serious risk of discriminatory bias in the use of AI in predictive policing systems. In this way, the need for mechanisms of transparency, responsibility and equity in the use of AI was confirmed in order to contain abuses and discriminatory practices. In this article, a qualitative approach was used through the bibliographic review technique using the hypothetical-deductive method.